Equity Beta for Regulated Energy Businesses in Australia: A Revisit - Pham, Thach Ngoc; Vo, Duc Hong (International Journal of Energy Economics and Policy, 2017)
This paper aims to estimate the equity beta – a key input of the Capital Asset Pricing Model, for the energy businesses in Australia in the 11-year period from 2005 to 2015. Various methods are used in this paper including Quantile Regression. Listed companies in the energy industry are considered at individual and portfolio levels. Findings from this paper are both consistent and contrast with prior related studies: (i) energy sector in Australia face a relatively low risk level compared to the market; (ii) OLS results are higher than LAD; and (iii) QR vary across different percentiles. Keywords: Equity Beta, Quantile regression, Australia. JEL Classifications: G11; G18